2014
DOI: 10.1186/1471-2474-15-341
|View full text |Cite
|
Sign up to set email alerts
|

Steroid injections added to the usual treatment of lumbar radicular syndrome: a pragmatic randomized controlled trial in general practice

Abstract: BackgroundLumbosacral radicular syndrome (LRS) is a self-limiting, benign, painful and impairing condition caused by lumbar disc herniation and inflammatory processes around the nerve root. Segmental epidural steroid injections (SESIs) are helpful to reduce radicular pain on a short-term basis. It is unknown whether SESIs are an effective addition to usual pain treatment of LRS in general practice. In our study, we assessed the effectiveness of SESIs on pain and disability as an addition to usual care for acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…However, only few studies have investigated the use of TEI specifically in patients with acute sciatica (< 8 weeks). One study randomized 63 patients with a duration of symptoms between 2 and 4 weeks to either TEI or usual conservative care [11]. The TEI group experienced a greater improvement in functionality and back pain, but differences between groups were small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few studies have investigated the use of TEI specifically in patients with acute sciatica (< 8 weeks). One study randomized 63 patients with a duration of symptoms between 2 and 4 weeks to either TEI or usual conservative care [11]. The TEI group experienced a greater improvement in functionality and back pain, but differences between groups were small.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this treatment would enable the patient to remain physically active while awaiting spontaneous recovery. Although its use is widespread, some patients experience a beneficial effect while others report no effect at all or only initial pain relief followed by recurrence of pain after several hours, days or weeks [11, 12]. In the Netherlands some hospitals offer TEI as standard care for sciatica but usually only after 14–16 weeks of conservative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, SpijkerHuiges et al 29 found a statistically significant effect of segmental epidural steroid injections on back pain, impairment and disability in acute lumbosacral radicular syndrome and patients from the intervention group were significantly more satisfied with the treatment received than patients from the control group. Moreover, Kim et al 30 found that repeated RF neurotomy for lumbar facet joint pain after microscopic discectomy is an effective palliative treatment and provided a mean duration of relief of 9.0 months and > 94% success rate.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to their inadequate efficacy in decreasing low back pain, focus has been shifted from the use of oral corticosteroids to epidural steroid injections. Furthermore, the evidence has demonstrated that the use of steroid injections alone or in combination with other modalities has improved symptoms, treatment satisfaction scores and cost-effectiveness in the management of low back pain ( Spijker-Huiges et al, 2014 , 2015 ). Spijker-Huiges et al (2014) demonstrated in a single-blinded, randomized controlled trial (RCT) improved treatment scores in a group of patients undergoing lumbar radicular syndrome treatment using segmental epidural steroid injections (SESIs) added to the usual pain treatments compared with control ( p = 0.006).…”
Section: Different Injectable Steroidsmentioning
confidence: 99%
“…Furthermore, the evidence has demonstrated that the use of steroid injections alone or in combination with other modalities has improved symptoms, treatment satisfaction scores and cost-effectiveness in the management of low back pain ( Spijker-Huiges et al, 2014 , 2015 ). Spijker-Huiges et al (2014) demonstrated in a single-blinded, randomized controlled trial (RCT) improved treatment scores in a group of patients undergoing lumbar radicular syndrome treatment using segmental epidural steroid injections (SESIs) added to the usual pain treatments compared with control ( p = 0.006). Another RCT demonstrated a significant improvement regarding the quality of life in the physical domain of the SF-36 questionnaire among patients utilizing SESIs compared to a control group in the management of lumbosacral radicular syndrome ( Spijker-Huiges et al, 2015 ).…”
Section: Different Injectable Steroidsmentioning
confidence: 99%